Transplantação renal em doentes com diabetes mellitus tipo I e tipo II - Baptista, C (1998)
A total of 618 patients with end-stage renal disease received kidney transplants between 1980 and September 1996. Twenty eight of them were diabetics. Better results were achieved for type 1 diabetic patients than for type 2 (mortality: 5.9% vs 27.3%; functioning graft: 88.2% vs 72.7%). The morbility was also higher in those patients (infections: 81.8% vs 29.4%; vascular complications: 45.5% vs 17.6%). Actuarial patient and graft survival were lower for type 2 than for non diabetic patients. For type 1 diabetics the results are similar to those for non diabetics. Better results can probably be achieved by restricting the selection criteria. The decision to transplant or maintain on dialysis should be made on a case by case basis.